Proses Adopsi Introduksi Sistem Tiga Strata (Sts) Di Manokwari Irian Jaya - Woran, Jonly; Yoku, Onesimus (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2006)
In Manokwari, Introduction Adoption Process of Three Strata Forage System (TSFS) is one way to improve productivity of grass along the year. The TSFS is an inovation to supply high quality grass to improve population of cattle. The relationship between cattle ownership with variables observability, compatibility and triability is significant, but with variables compiexity and relative advantage is non significant. The variables have significant value showed that the degree of relationship association is high enough. Model of TSFS can be applied by peasant based on the preference of individual peasant.